Providing Out-of-School Adolescent Girls with Skills : A Review of the Global Evidence - Chakravarty, Shubha (World Bank, Washington, DC, 2016)
Skills development offers a range of benefits to out-of-school adolescent girls and alleviates a key obstacle to youth employment in developing countries. But do increased skills lead to delays in early marriage and pregnancy? Not always, according to the available empirical evidence. Although the global evidence base on skills training is growing, and despite a theoretical basis for the relationship between skills, employment and fertility, the documented impacts of skills interventions on fertility outcomes are still too limited to draw strong conclusions. The substantial heterogeneity of what constitutes a “skills” intervention contributes to the uncertainty. The strongest evidence is in support of holistic community-based programs that combine information on sexual and reproductive health with skills training and other financial and social assets. More research is needed to isolate the impacts of these different program components and disentangle the causal pathways leading to delays in marriage and pregnancy.